2016
DOI: 10.1097/ccm.0000000000001397
|View full text |Cite
|
Sign up to set email alerts
|

Kidney and Liver Injuries After Major Burns in Rats Are Prevented by Resolvin D2

Abstract: Background Innate immune dysfunction after major burn injuries increases the susceptibility to organ failure. Lipid mediators of inflammation resolution, e.g. Resolvin D2 (RvD2), have been shown recently to restore neutrophil functionality and reduce mortality rate in a rat model of major burn injury. However, the physiological mechanisms responsible for the benefic activity of RvD2 are not well understood. Design Prospective randomized animal investigation. Setting Academic research setting. Subjects Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…RvD2 is a potent immunoresolvent that stereoselectively reduces excessive PMN trafficking in peritonitis and improves survival in sepsis (19). RvD2’s potent nanogram actions are also protective in disease models where RvD2 prevents inflammatory bowel disease such as colitis (22), alleviates inflammatory and fibromyalgia-induced pain (23, 24), increases survival following burn wound and reduces kidney and liver injuries in mice (25, 26), periodontitis (27) as well as nerve injuries as seen in Parkinson’s disease (28). …”
Section: Introductionmentioning
confidence: 99%
“…RvD2 is a potent immunoresolvent that stereoselectively reduces excessive PMN trafficking in peritonitis and improves survival in sepsis (19). RvD2’s potent nanogram actions are also protective in disease models where RvD2 prevents inflammatory bowel disease such as colitis (22), alleviates inflammatory and fibromyalgia-induced pain (23, 24), increases survival following burn wound and reduces kidney and liver injuries in mice (25, 26), periodontitis (27) as well as nerve injuries as seen in Parkinson’s disease (28). …”
Section: Introductionmentioning
confidence: 99%
“…9, 10, 11 NET formation is involved in inflammatory responses, such as thrombosis and tissue injury. 12, 13, 14, 15 Although eosinophils, mast cells, monocyte and chronic myelocytic leukemia cell-derived neutrophils have been reported to release ETs, 16, 17, 18, 19, 20, 21 it remains unclear whether immature granulocytes like APL cells undergo ETosis. Recent reports showed that differentiation of HL-60 cells, a human promyelocytic leukemia cell line, into mature neutrophils with calcium ionophore, ATRA, or dimethyl sulfoxide or exposure to the glycosyltransferase inhibitor tunicamycin (TM) resulted in the formation of NET-like structures.…”
mentioning
confidence: 99%
“…17 This chain of events could explain the association between major burn injury and subsequent acute tubular necrosis and liver injury. 18 In other conditions, the trapping of NETs in capillaries may have a beneficial effect. For example, chromatin released during inflammation in a tissue is likely to be transported to the lung, where it is mechanically trapped by the dense capillary network of the alveolae.…”
Section: Discussionmentioning
confidence: 99%